Chess as an extracurricular activity - Martinović, Saša, pedagog (Array, 2020)
Extracurricular activities as a variety of organizational forms of students gathering in free extracurricular time at elementary school have predominantly cultural, artistic, sporting, technical, recreational or scientific character (Cindrić, 1992). Through them, students meet their needs and develop the culture of using their leisure time. Thanks to its pedagogic potential, chess is increasingly used as an educational tool and taught in elementary schools around the world. This trend begins to follow Croatia, where chess in many schools is carried out as an extracurricular and/or extracurricular activity. In this paper we will present and analyze the advantages that chess has for the elementary school students and empirically determine the occurrence of chess as an extracurricular activity in the schools in the City of Zagreb. Also, based on the results of the qualitative research, the views of the chess teachers regarding advantages of chess implementation, ways of determining the interests of students, and teaching methods used in chess teaching will be presented.